The Impact of BIM on Construction Cost Industry in the Era of Big Data and Countermeasure Analysis - Xu, Xiuhua (Journal of Theory and Practice of Management Science, 2023)
In the engineering cost management,BIM technology has obvious advantages in data acquisition, information analysis and processing and engineering quantity calculation. Based on this, when organizing project cost management, it is necessary to fully explore the advantages of BIM technology and improve the level of project cost management through complementary advantages.